Analysis on the influence of opening and closing of ventilation tunnel on radon concentration distribution. Issue 2 (January 2021) - Yang, Jianchuan; Wang, Shuguang; Wang, Chunyan; Ba, Long
Abstract: Meteorological ventilation conditions affect easily on radon concentration in granite tunnel. In this paper, the variation of radon concentration in the tunnel in natural and ventilation conditions is analyzed through numerical simulation method. It is found that the radon concentration in tunnel can be effectively controlled by closing the tunnel entrance under the condition of pressurized ventilation.